Stabilization studies of Fomes sclerodermeus laccases - Papinutti, Víctor Leandro (2008)
Stability of laccase isoenzymes from a crude extract obtained from Fomes sclerodermeus grown on wheat bran medium was studied. The variables assessed were temperature, pH and additives. As revealed by PAGE, three bands of laccase, each with different thermal inactivation pattern, were detected in the crude extract: after 6 h at 50 °C and pH 8, Lc2 was the most resistant, while the Lc1 and Lc3 bands were almost completely inactivated. This pattern of inactivation was observed at all temperatures and pH tested. Laccase activity was more stable in the 5-10 pH range when incubated at 40 and 50 °C; at 30 °C and 24 h the enzyme remained fully active in the 3-11 pH range. The effect of additives (veratryl alcohol, trehalose, glycerol, mannitol, glutaraldehyde, CuSO4 and 1-HBT) on laccase stability was tested. The stability was enhanced with CuSO4 (1.25 mM), glycerol (0.2%) and mannitol (1%). The presence of both CuSO4 and glycerol caused a 3-fold increase in the half-life values.